2015
DOI: 10.1002/2014wr016496
|View full text |Cite
|
Sign up to set email alerts
|

Canopy influence on snow depth distribution in a pine stand determined from terrestrial laser data

Abstract: In this study, we analyzed the effects of the forest canopy and trunks of a pine stand in the central Spanish Pyrenees on the snow depth (SD) distribution. Using LiDAR technology with a terrestrial laser scanner (TLS), high-resolution data on the SD distribution were acquired during the 2011-2012 and 2012-2013 snow seasons, which were 2 years having very contrasting climatic and snow accumulation conditions. Average SD evolution in open and canopy areas was characterized. Principal component analysis was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 58 publications
2
38
1
Order By: Relevance
“…The increased depth hoar development in canopy gaps may have occurred because the snow was deeper in these locations at a time when kinetic metamorphism was dominating. In this regard, previous works have shown that differences in snow depth between gaps and under the canopy are greater when the snowpack is thinner [ López‐Moreno and Latron , 2008; Revuelto et al ., ]. The increased development of depth hoar in canopy gaps is somewhat counter‐intuitive because, mathematically, temperature gradients must decrease when snow depth increases.…”
Section: Discussionmentioning
confidence: 99%
“…The increased depth hoar development in canopy gaps may have occurred because the snow was deeper in these locations at a time when kinetic metamorphism was dominating. In this regard, previous works have shown that differences in snow depth between gaps and under the canopy are greater when the snowpack is thinner [ López‐Moreno and Latron , 2008; Revuelto et al ., ]. The increased development of depth hoar in canopy gaps is somewhat counter‐intuitive because, mathematically, temperature gradients must decrease when snow depth increases.…”
Section: Discussionmentioning
confidence: 99%
“…Snow accumulation across the mountains is primarily influenced by orographic processes, involving feedbacks between atmospheric circulation and terrain (Roe, 2005;Roe and Baker, 2006). In most forested regions, snow distribution is highly sensitive to vegetation structure (Anderson, 1963;Revuelto et al, 2015;Musselman et al, 2008), and canopy interception, sublimation and unloading result in less accumulation of snow beneath the forest canopies in comparison with canopy gaps (Berris and Harr, 1987;Golding and Swanson,…”
Section: Introductionmentioning
confidence: 99%
“…High spatial resolution information on the distribution of the snowpack on different days was obtained using a TLS (that uses LiDAR technology for measuring distances); these devices have been used extensively for monitoring snow evolution [36,37,41,42] recently reported the use of a TLS (RIEGL LPM-321) for analysis of snowpack dynamics in the same study area as was used in this study. Following the pruning that occurred in summer 2013, the snowpack distribution was assessed on seven additional dates using the same data acquisition protocol [11]; this enabled direct comparison with the data collected under pre-pruning conditions. Based on results presented in this study, we decided to not include data from four TLS surveys collected during the 2011-2012 snow season, as the snow distribution was clearly driven by an anomalous wind redistribution event, and was not comparable to conditions observed during the snow season following pruning.…”
Section: Methodsmentioning
confidence: 99%
“…Varimax rotation [47,48] was applied to distinguish components having physically consistent patterns. The PCA analysis was applied to the dataset of 11,000 grid cells of snow depth distribution data for each of the 23 TLS survey days. With this analysis, the survey dates were classified in the different components considering the highest correlation with the components.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation